ASEAN in the Midst of Global Polycrisis: A Reflection - Syukur, Yanuardi (Pubmedia Social Sciences and Humanities, 2025)
Currently, the global world, including ASEAN, is facing various crises or polycrisis. This article tries to explain what ASEAN needs to do to get out of the polycrisis. The article is arranged in the form of a reflection on the dynamics of ASEAN in facing polycrisis. This article shows some input for ASEAN to get out of the polycrisis, namely maintaining stability amidst turmoil; maintaining ASEAN as the epicenter of economic growth; preventing erosion of social cohesion and polarization of society and implementing extraordinary tactical strategies, namely ‘the way forward, the way of collaboration’. This article also emphasizes the importance of cultural aspects in maintaining friendship between ASEAN communities and countries in facing global polycrisis.